The Existence of Carbon Trading Through Profitability and Carbon Emission Disclosure as a Concretization of Net Zero Emission - Hanifah, Umi; Meikhati, Ety (LPPM Universitas Duta Bangsa Surakarta, 2024)
Global warming and climate change are problems that require entities or companies to respond to these phenomena, so hat companies are required to be responsible for environmental problems related to emissions resulting from company activities. This research aims to determine the effect of profitability and carbon emission disclosure on trading carbon in energy sector companies listed on the IDX in 2017-2021. This research usesa quantitative approach. Data analysis techniques use descriptive statistical analysis, calssical assumption testing and hypothesis testing. The research result show that profitability has no effect on trading carbon, while carbon emission disclosure as an effect on trading carbon. Profitability and carbon emission disclosure effect simultaneously on the trading carbon.